Functional and Biochemical Analysis of the Type 1 Inositol (1,4,5)-Trisphosphate Receptor Calcium Sensor - Tu, Huiping (Biophysical Society, 2003)
Modulation of the type 1 inositol (1,4,5)-trisphosphate receptors (InsP(3)R1) by cytosolic calcium (Ca(2+)) plays an essential role in their signaling function, but structural determinants and mechanisms responsible for the InsP(3)R1 regulation by Ca(2+) are poorly understood. Using DT40 cell expression system and Ca(2+) imaging assay, in our previous study we identified a critical role of E2100 residue in the InsP(3)R1 modulation by Ca(2+). By using intrinsic tryptophan fluorescence measurements in the present study we determined that the putative InsP(3)R1 Ca(2+)-sensor region (E1932–R2270) binds Ca(2+) with 0.16 μM affinity. We further established that E2100D and E2100Q mutations decrease Ca(2+)-binding affinity of the putative InsP(3)R1 Ca(2+)-sensor region to 1 μM. In planar lipid bilayer experiments with recombinant InsP(3)R1 expressed in Spodoptera frugiperda cells we discovered that E2100D and E2100Q mutations shifted the peak of the InsP(3)R1 bell-shaped Ca(2+) dependence from 0.2 μM to 1.5 μM Ca(2+). In agreement with the biochemical data, we found that the apparent affinities of Ca(2+) activating and inhibitory sites of the InsP(3)R1 were 0.2 μM for the wild-type channels and 1–2 μM Ca(2+) for the E2100D and E2100Q mutants. The results obtained in our study support the hypothesis that E2100 residue forms a part of the InsP(3)R1 Ca(2+) sensor.